Avaliação de recuperação ambiental no garimpo semimecanizado de diamantes da Chapada Diamantina, Bahia - Lima, Alisson (2018)
For the first time in Chapada Diamantina, a group of prospectors have organized to facilitate the continuity of the prospecting and mining of diamonds, established in 2001 the Prospectors' Cooperative of Andaraí (COOGAN). COOGAN, who obtained authorization for the realization of mineral inquiry in the area between 2006 - 2013, is responsible for the environmental recovery of the degraded area of current mines, presenting a new formalized perspective of the exploitation of the alluvia diamantiferous, in the areas known as Santa Rita and Pau D'óleo. The most recent cycle of the mines of this region uses semi-mechanized techniques for sterile removal of sediments and for dredging of the layer of diamantiferous gravel. As any human action, this type of mining causes impacts to the environment, being able to contribute directly to environmental degradation, with emphasis to the destruction and / or alteration of vegetation, physio-chemical characteristics of the solo and water bodies in the adjacent mines, interfering with river courses and drainage standards. In this context, the minimization of the impacts of the exploited manual extration on the environment and the necessity of recovery of the degraded areas are key points for conflict resolution due to the mining prospects of diamonds that at present takes place in the vicinity of the Paraguaçu river, in the municipality of Andaraí. This research characterizes the alluvial deposits goal of mining prospects, characterized by the current forms of mining of the prospectors identifying its environmental impacts and contributing with proposals for formalizing and environmental adaptation of the small and middle miners through cooperatives and ratifying the importance of public policies that help the mine to support itself in accordance with environmental legislation. For this reason, this study will carry out an evaluation of the progressive rehabilitation of areas that were already recovered by the cooperative, noticing if the recuperation reached the standards recommended by the Brazilian mineral and environmental legislation and proposing a model of sustainable plowing.